The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/09612033221133684
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of the predictive urinary exosomal miR-195-5p in lupus nephritis based on renal miRNA-mRNA co-expression network

Abstract: Objective Lupus nephritis (LN) is the main complication of systemic lupus erythematosus (SLE), causing huge financial burden and poor quality of life. Due to the low compliance of renal biopsy, we aim to find a non-invasive biomarker of LN to optimize its predictive, preventive, and personalized medical service or management. Method Herein, we provided a bioinformatic screen combined clinical validation strategy for rapidly mining exosomal miRNAs for LN diagnosis and management. We screened out differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Chen et al (39) found that exosomes derived from umbilical cord blood-derived MSCs could alleviate diffuse alveolar hemorrhage in SLE mice and demonstrated that exosomes from umbilical cord blood-derived MSCs could transport miR-146-5p to target and inhibit the expression of NOTCH1, thus promoting the polarization of M2 macrophages, leading to the suppression of excessive inflammatory responses and protection against alveolar injury. Cheng et al (40) demonstrated downregulation of miR-195-5p in the urine of lupus nephritis patients and its negative modulation of CXCL10, consistent with their initial result based on online available data. Furthermore, this miRNA was negatively correlated with urinary protein, renal damage, serum complement levels, and disease severity.…”
Section: Exosomal Mirnas In Systemic Lupus Erythematosussupporting
confidence: 64%
“…Chen et al (39) found that exosomes derived from umbilical cord blood-derived MSCs could alleviate diffuse alveolar hemorrhage in SLE mice and demonstrated that exosomes from umbilical cord blood-derived MSCs could transport miR-146-5p to target and inhibit the expression of NOTCH1, thus promoting the polarization of M2 macrophages, leading to the suppression of excessive inflammatory responses and protection against alveolar injury. Cheng et al (40) demonstrated downregulation of miR-195-5p in the urine of lupus nephritis patients and its negative modulation of CXCL10, consistent with their initial result based on online available data. Furthermore, this miRNA was negatively correlated with urinary protein, renal damage, serum complement levels, and disease severity.…”
Section: Exosomal Mirnas In Systemic Lupus Erythematosussupporting
confidence: 64%
“…The identification of relevant miRNAs involved in LN kidney recovery may aid in the development of new therapeutic approaches [83]. Urinary exosomal miR-195-5p, miR-25-3p, and miR-429 were all downregulated in patients, and miR-195-5p was able to distinguish LN patients from SLE with high sensitivity and specificity, indicating a promising future for LN disease monitoring and diagnosis [87]. Let-7a and miR-21, two miRs known to be differentially expressed in LN tissues and/or serum, were downregulated in urinary exosomes during an active flare of LN [88].…”
Section: Lupus Nephritismentioning
confidence: 99%
“…Perez-Hernandez et al [ 151 ] further discovered that urinary exosomal miR-146a was not only serving as a biomarker of albuminemia, correlating with lupus activity, proteinuria, and histological features to discriminate individual LN patients, but also represented as a good baseline marker for SLE flares. Cheng et al [ 152 ] used a bioinformatic screen combined with clinical validation to rapidly extract the exosomal miRs for an LN diagnosis and management. The group screened out differentially expressed miRs and mRNAs in the LN database.…”
Section: Current Useful Biomarkers In the Renal Tissues Of Patients W...mentioning
confidence: 99%
“…Urinary exosomal miRs: miR-29c for early renal fibrosis [ 147 ] miR-21, miR-29c, miR-150 for early renal fibrosis [ 148 ] miR-21↓ and let-7c↓ for LN disease flare [ 149 ] miR-135p for treatment responder patients [ 150 ] miR-146a for disease flare [ 151 ] miR-195-5p as disease biomarker [ 152 ] …”
Section: Figurementioning
confidence: 99%